Minimização da formação de B-30 Destreonina Insulina durante a conversão enzimática da Proinsulina em insulina por Tripsinólise - Jane Cristina Rodrigues da Cruz (2010)
The present study was conducted at the effective blockade of ε-amino group of lysine residues of chain B of Insulin, Insulin and Proinsulin before enzymatic conversions caused by the combined use of Trypsin and Carboxypeptidase B limiting the restriction site of these enzymes to Arginine residues and thus decreasing substantially the presence of intermediate B-30 Destreonin Insulin during the industrial production of human insulin. The proposed conditions are: concentration of 100:1 reagent over the sample in Glycine buffer pH 9,0, temperature 23°C with immediate correction of pH. The enzymatic conversions were carried out under the above conditions and every two hours of conversion the products were analyzed by reverse phase HPLC chromatography and mass spectrometry MALDI-TOFMS/MSMS and Q-TOFMS. The full scan profile obtained by Maldi TOF detected a reduction of the ions of Proinsulin m/z 10633 and the increase of the ion m/z 5808 of Insulin. The presence of the ion corresponding to B-30 Destreonin was not observed when the analysis was made by Maldi TOF, possibly due to suppression caused by other ions in the sample conversion whose relative intensity was high. When analyzed by Q-TOF, the conversion profile of the spectrum presented Proinsulin blocked and not blocked with 2,3-dimetylmaleic shows the decrease in relative intensity of multicharger ions m/z 1902 and 1427 related to m/z 5707, suggesting the presence of B -30 Destreonina Insulin. As reference ion was followed by the presence of m/z 1256 for the component Histidine tail that keeps the relative intensity of the Q-TOF MS analysis of samples with and without blocking ε-amino corroborating with the proposed treatment for minimization of the formation of B-30 Destreonina Insulin compound.